Excessive internet use in European adolescents: what determines differences in severity? - Blinka, Lukas; Škařupová, Kateřina; Ševčíková, Anna; Wölfling, Klaus; Müller, Kai W; Dreier, Michael (International journal of public health, 2015)
OBJECTIVES: This study investigated the differences between non-excessive, moderately excessive, and highly excessive internet use among adolescents. These differences were explored in terms of personal characteristics, psychological difficulties, environmental factors, and manner of internet use. METHODS: A representative sample was investigated, consisting of 18,709 adolescents aged 11-16 and their parents, from 25 European countries. Excessive internet use was measured using a five item scale covering following factors: salience, conflict, tolerance, withdrawal symptoms, and relapse and reinstatement. The main data analysis utilised multinomial and binary logistic regression models. RESULTS: The vast majority of respondents reported no signs of excessive internet use. Moderately excessive users (4.4%) reported higher emotional and behavioural difficulties, but also more sophisticated digital skills and a broader range of online activities. The highly excessive users (1.4%) differed from the non-excessive and moderately excessive users in their preference for online games and in having more difficulties with self-control. CONCLUSIONS: Adolescents who struggle with attention and self-control and who are inclined toward online gaming may be especially vulnerable to the otherwise uncommon phenomenon of excessive internet use.
Keywords: Odds Ratio; Risk Assessment; lidé; mladiství; odds ratio; Behavior, Addictive; internet; Female; dítě; Evropa; průzkumy a dotazníky; interval spolehlivosti; Attention; hodnocení rizik; Multivariate Analysis; chování mladistvých; multivariační analýza; Adolescent; Humans; Self Concept; průřezové studie; videohry; návykové chování; Cross-Sectional Studies; pozornost; Adolescent Behavior; Confidence Intervals; logistické modely; mužské pohlaví; sebepojetí; duševní zdraví; Time Factors; ženské pohlaví; Logistic Models; časové faktory; Male; Europe; Mental Health; Video Games; Internet; Child; Surveys and Questionnaires